2011
DOI: 10.1179/026708310x12683157551577
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics and abrasive wear resistance of boride layers on Fe–15Cr alloy

Abstract: Two boride layers based on the FeB and Fe 2 B compounds are formed at the interface between an Fe-15Cr alloy and boron at 850-950uC and reaction times up to 12 h, with the average chromium content being around 8 at-% in the former and 12 at-% in the latter. Both boride layers reveal a pronounced texture. Diffusional growth kinetics of the layers are close to parabolic and can alternatively be described by a system of two non-linear differential equations. Microhardness values are 17?4 GPa for the FeB layer, 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
19
0
2
Order By: Relevance
“…In this case, an alternative diffusion model for the estimation of the growth kinetics of boride layers proposed by Dybkov et al [12] was adopted in this study. Basically, the model is related to the chemical reactions that occur at the growth interphase and the changes of thickness of the layers due to those reactions.…”
Section: Growth Kinetics Of Cob-co 2 B Layers During the Pbcdf Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, an alternative diffusion model for the estimation of the growth kinetics of boride layers proposed by Dybkov et al [12] was adopted in this study. Basically, the model is related to the chemical reactions that occur at the growth interphase and the changes of thickness of the layers due to those reactions.…”
Section: Growth Kinetics Of Cob-co 2 B Layers During the Pbcdf Processmentioning
confidence: 99%
“…In this study, the CoCrMo alloy was borided using the PBDCF process developed CoB-Co 2 B layers at 1,098-1,148 K with different exposure times. The kinetics of the cobalt boride layers was estimated using a diffusion model proposed by Dybkov et al [12], which considers a system of two differential equations to obtain the growth constants of both CoB and Co 2 B. The results of the growth constants obtained by the diffusion model were expressed as Arrhenius relationships in the set of experimental temperatures to verify the effect of the current field on the activation energies of boron in the CoB and Co 2 B.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of borided high chromium steel, the properties remain similar: Dybkov et al even found a strong increase of the abrasive wear resistance when the chromium content increases in the substrate [26]. The boriding layers are also appropriate for cyclic oxidation conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…The best abrasive wear strengths were obtained in boronizing for 8 h at 900°C for SAE 1010 and SAE 1040 steels, 4 h at 900°C for D2 steel, and 6 h at 900°C for 304 steel. In another work [13], abrasive wear resistance of boride layers on Fe-15Cr alloy was studied. It was found that the dry abrasive wear resistance of borided alloy samples was around 45 times greater than that of non-borided ones.…”
Section: Introductionmentioning
confidence: 99%